Índices de evasão dos cursos na Universidade de Brasilia - Kipnis, Bernado; Bareicha, Paulo; Taveira, Ana Cláudia; Magalhães, Cristina; Assis, Marta H. de; Oliveira, Tânia Pinfildi de (Linhas Críticas, 1998)
Resumo